2021
DOI: 10.1371/journal.pone.0253828
|View full text |Cite
|
Sign up to set email alerts
|

Implication of β2-adrenergic receptor and miR-196a correlation in neurite outgrowth of LNCaP prostate cancer cells

Abstract: The β2-adrenergic receptor has been shown to be involved in neuroendocrine differentiation and to contribute to the development of aggressive prostate cancer. In this study we have investigated whether miR-196a plays a role in the regulation of the β2-adrenergic receptor in the LNCaP prostate cancer cell line. Our results show that the expression of miR-196a is elevated in LNCaP prostate cancer cells with reduced levels of β2-adrenergic receptor after stably transfection with three different shRNAs. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The autonomic nervous system has been observed to exert a considerable impact on the development and progression [ 20 ]of prostate cancer. Studies have demonstrated a significant increase in sympathetic nerve activity [ 21 , 22 ]n tissues linked to high-risk prostate cancer, with β2AR [ 6 , 7 , 23 , 24 ] playing a vital role in the sympathetic nervous system signaling pathway. The analysis of the results revealed that patients who used propranolol for a long period of time experienced prolonged periods of survival [ 8 , 9 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic nervous system has been observed to exert a considerable impact on the development and progression [ 20 ]of prostate cancer. Studies have demonstrated a significant increase in sympathetic nerve activity [ 21 , 22 ]n tissues linked to high-risk prostate cancer, with β2AR [ 6 , 7 , 23 , 24 ] playing a vital role in the sympathetic nervous system signaling pathway. The analysis of the results revealed that patients who used propranolol for a long period of time experienced prolonged periods of survival [ 8 , 9 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Petiwala’s study revealed that CA exhibited suppressive effects in prostate cancer by promoting proteasomal degradation of the androgen receptor (AR) by inducing ER stress ( Petiwala et al ., 2016 ). The androgen receptor is a molecular target for prostate cancer treatment; however, these receptors can develop resistance by increasing AR levels or inducing AR mutations for survival after androgen therapy ( Guerriero et al ., 2021 ).…”
Section: The Effect Of Rosmarinic Acid and Carnosic Acid On Different...mentioning
confidence: 99%